Growing space in a 35-year-old Pinus taeda stand - Gorgete Santos, Marina; Silvestre Lima Sanson, Caio; Paulo Sardo Madi, João; Behling, Alexandre; Dobner Júnior, Mário; Tyszka Martinez, Diego (Scientia Agraria Paranaensis, 2021)
Considering the economic importance of the Pinus species in Brazil, especially in the southern region, this study was carried out to fill some gaps and assist in the production processes of this species. The specific objective was to evaluate the influence of different growing space regimes in experimental plantations of Pinus taeda L., aged 35 years, without thinning, located in the state of Santa Catarina. Diameter at breast height (DBH) and total height data were collected, and the Gamma and Weibull (3P) probability density functions (PDF) were used to describe the structure of the diameter and height variables, respectively. Then multivariate analysis and discriminant functions were applied to identify the correlation of these variables. For qualitative variables, tree health was assessed in three classifications: 1 - Healthy, with no apparent damage; 2 - Initial stage of deterioration by pests and/or diseases; and 3 - Advanced stage of deterioration by pests and/or diseases. The trunk quality variable was also evaluated in three classifications: 1 - Trunk without apparent defects; 2 - Slightly crooked trunk, however cylindrical and devoid of considerable ramifications; and 3 - Trunk with strong tortuosity or bifurcation. The results showed that growing space directly affected the average diameter. Stands with greater space per tree maximized the variables when considering height and DBH together. Stands with less growing space, on the other hand, favored better trunk quality, and the dominant individuals in height had superior health and trunk quality compared to the others.